Tea or Thrush?: A Case of Nonaccidental Oral Injury in an Infant - Jan, Meryam; Dully, Kathleen; Kostecki, Carissa; Alexander, Randell C. (Journal of Child Science, 2021)
A 5-month-old girl child patient presented to the emergency department for oral thrush and poor feeding but instead demonstrated concern for abuse after physical exam, as findings were consistent with oral injury. Correct identification of the oral findings as traumatic necessitated navigating language and cultural issues before the mechanism of injury and abuse determination could be made. Exploring the involvement of other caregivers was a crucial piece for investigation of the clinical scenario. The incidence of child abuse and pediatric oral injuries concerning for abuse were reviewed in this case report.
Keywords: burns; child abuse; child neglect; oral injury